PHASE DIAGRAMS OF THREE-COMPONENT SYSTEMS AS A BASIS FOR THE ANALYSIS OF METASOMATIC PROCESSES - Treivus E.B. (My University, 2004)
Ternary phase diagrams were explored in detail and refined for their use in the analysis of metasomatic processes. It was shown that crystallization pressure is not the main source of this process. The conditions of equivolume replacement during metasomatism were evaluated. It was concluded that replacement processes always accompany the dissolution of a polymineralic rock.